2022
DOI: 10.1089/ast.2022.0027
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Synthesis of Polyribonucleic Acid on Prebiotic Rock Glasses

Abstract: Reported here are experiments that show that ribonucleoside triphosphates are converted to polyribonucleic acid when incubated with rock glasses similar to those likely present 4.3–4.4 billion years ago on the Hadean Earth surface, where they were formed by impacts and volcanism. This polyribonucleic acid averages 100–300 nucleotides in length, with a substantial fraction of 3′,-5′-dinucleotide linkages. Chemical analyses, including classical methods that were used to prove the structure of natural RNA, establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Using activated nucleotides, they were able to form RNA polymers up to 40 mers. More recently, rock glasses have been used to convert ribonucleosides 5′-triphosphates into RNA long of 9–150 mers on average [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using activated nucleotides, they were able to form RNA polymers up to 40 mers. More recently, rock glasses have been used to convert ribonucleosides 5′-triphosphates into RNA long of 9–150 mers on average [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meteorite impact with planetary bodies is proposed as a possible route to their delivery as the course of their origin on Earth and other planets. Recently, it has been shown that the catalytic synthesis of polyribonucleic acids from ribonucleoside triphosphates is possible on prebiotic rock glasses, which resemble the rock on Hadean Earth surface formed by volcanic activities and impacts (Jerome et al, 2022). It is probable that such rock materials, silicates, and minerals in dust grains in the interstellar medium can catalyze similar chemical transformations resulting in molecular evolution to complex systems such as RNA from simple systems.…”
Section: Methanol a Key Synthon Toward Complex Organic Moleculesmentioning
confidence: 99%
“…Catalytic surfaces including clays, minerals, rocks, glasses and even meteoritic dust, have also been explored as means of increasing rates of synthesis and polymerization of prebiotic molecules including amino acids, nucleic acids, peptides and polynucleic acids [ 12 , 54 , 55 , 56 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. The literature concerning the use of such natural catalytic surfaces is so large that no attempt is made here to encompass its range.…”
Section: Introductionmentioning
confidence: 99%